Alternating Bi-Weekly Intravitreal Ranibizumab and Bevacizumab for Refractory Neovascular Age-Related Macular Degeneration with Pigment Epithelial Detachment*. (4th May 2017) - Witkin, Andre J.; Rayess, Nadim; Garg, Sunir J.; Maguire, Joseph I.; Storey, Philip; Kaiser, Richard S.; Hsu, Jason; Vander, James F.; Ho, Allen C.
Abstract: Objective : To describe visual and anatomical outcomes following bi-weekly intravitreal ranibizumab/bevacizumab injections in eyes with refractory neovascular age-related macular degeneration (AMD) and pigment epithelial detachment (PED). Design : Retrospective, consecutive, interventional case series. Participants : Eighteen patients diagnosed with neovascular AMD that were refractory to anti-VEGF therapy and received alternating biweekly ranibizumab/bevacizumab injections were included. Methods : Patients with neovascular AMD and PED that were refractory to at least 11 monthly ranibizumab or bevacizumab injections were included in this study at a large, single retina practice. Following inclusion, patients received four bi-weekly alternating ranibizumab/bevacizumab intravitreal injections. After completing a course of four bi-weekly injections, patients were treated with variable regimens of intravitreal anti-vascular endothelial growth factor (VEGF) therapy. The primary outcomes of the study included change in visual acuity (VA) and central foveal thickness (CFT) at eight weeks follow-up. Results : Study eyes had previously received a mean of 22 intravitreal anti-VEGF injections. At enrollment, mean VA was 20/95 and mean CFT was 455 µm. After four bi-weekly anti-VEGF injections, mean VA improved to 20/65 ( p < 0.001), and mean CFT decreased to 387 µm ( p = 0.029). In patients with PED, there was a mean 27.9% reduction in height ( p = 0.046) at eight weeks' follow-up. Conclusions : Four injections of bi-weekly alternating ranibizumab/bevacizumab improved visual acuity and reduced macular thickness in a number of patients with refractory neovascular AMD and PED.